Effect of different planting time and varieties on Growth and Yield of African Marigold (Tagetes erecta) in the Kavre district, Nepal - Dhakal, Mira; Pun, Amar Bahadur; Bhattarai, Shandesh (Nepal Journal of Science and Technology, 2021)
A field experiment was conducted to study the effect of different planting time on growth and flowering attributes of different varieties of African marigold at Kavre district of Nepal during the year of 2014 to 2017. The experiment consisted of four replications and was laid out in a two factorial RCB design. Six treatment combinations consisting of two open pollinated varieties of marigold viz. Calcattia Orange and Calcattia Yellow and three planting time viz. 1st January 2015, 15th February 2015 and 30th March 2015 were evaluated. The pooled analysis of two years’ data showed a significant influence of varieties and planting dates on vegetative growth and flower yield and yield attributing characters Flowering duration differed significantly with variety and its interaction with date of planting. Longer duration of flowering was observed by Calcattia Orange (57.58 days) followed by Calcattia Yellow (53.50 days). 1st January planting of Calcattia Orange exhibited significantly the longest flowering duration (62.00 Days). The flower yield per plant was the highest in Calcattia Orange (894.3 gm/plant) than Calcattia Yellow (815.3 gm/plant). Similarly, 1st January planting had the highest flower yield/plant (1033.1 g/plant) followed by 15th February planting (854.9 gm/plant) and 30th March planting (676.4 g/plant). Although not significant, Calcattia Orange planted on 1st January showed better results in terms of Flower yield /plant (1081 g), Number of flowers per plant and flower size as compared to other treatment combinations and significantly the highest duration of flowering (62.00 days) along with attractive orange color under Kavre condition.